The nucleon momentum distribution in light nuclei - Ypsilantis, K. N.; Grypeos, M. E. (HNPS Advances in Nuclear Physics, 2020)
The nucléon momentum distribution in light nuclei is studied by means of a single particle potential model which consists of an attractive harmonic oscillator potential Va=½mω²r² and also of a repulsive one of the form Vr=B/r², Β > 0. The latter simulates to some extend effects which would result if short range correlations were included (e.g. by a Jastrow factor) in a nuclear wave function, having as uncorrelated part a Slater determinant of harmonic oscillator orbitals. The main advantage of this model is that it leads to fairly simple analytic expressions for the momentum distribution of light nuclei and also for the density distributions and the elastic form factors. These expressions are quite useful in obtaining, for example, the asymptotic form of η(k) for large k from which it is seen that the steep decrease of the nucléon momentum distribution observed with the harmonic oscillator model in this region is improved. Numerical results using various least squares fittings are obtained and discussed for a number of nuclei of the 1s, 1p shell.